Biomass-based polyfuran high polymer material and preparation method thereof
By polymerizing the downstream product of HMF with bis-(5-formyl furfuryl) ether and ketone, biomass-based polyfuryl polymer material with furan ring, carbon-carbon chain, and C-O-C bond was prepared, which solved the problem of insufficient mechanical properties and heat resistance of existing biomass-based polymer materials, achieved high performance and recyclability of the material, and expanded its application range.
Patent Information
- Application Number
- CN202510114820.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing bio-based polymer materials have shortcomings in terms of mechanical properties and heat resistance, which limits their application range and is difficult to replace petroleum-based polymer materials.
By using raw materials such as bis-(5-formylfurfuryl)ether (OBMF) downstream of HMF, polymerization under the action of a catalyst, biomass-based polyfuran polymer material containing furan ring, carbon-carbon chain, and C-O-C bond in the molecular structure was prepared.
The material has an absorption signal in the visible or ultraviolet region, has excellent barrier properties, heat resistance and mechanical properties, can achieve 100% recycling, and is suitable for photoelectric materials, energy materials, catalytic materials, packaging materials and adsorption materials.
Smart Images

Figure BDA0005257584380000051 
Figure BDA0005257584380000061 
Figure BDA0005257584380000062
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass-based green polymer materials, and the specific material is a biomass-based polyfuran polymer material and a preparation method thereof. Background Art
[0002] The Ministry of Industry and Information Technology, the Ministry of Ecology and Environment, the Ministry of Emergency Management, and the National Standards Administration jointly issued the "Action Plan for Improving Standards to Lead the Optimization and Upgrading of the Raw Materials Industry (2025-2027)". The action plan clearly classifies degradable materials as advanced basic materials and bio-based new materials as key strategic materials. It requires that the high-quality development of key industrial chains be promoted, application scenarios and industrial research and development be closely integrated, and the development and implementation of key standards be promoted simultaneously.
[0003] Biomass-based materials refer to a new type of materials made from renewable biomass or raw materials obtained through biological manufacturing through biological, chemical, physical and other means, such as bioplastics, biomass functional polymer materials, etc. Bio-based materials are different from traditional chemical materials produced from non-renewable petrochemical resources such as coal and oil. They have the characteristics of renewable raw materials, reduced carbon emissions, and energy conservation. Some categories also have good biodegradability, and are an important direction for the development of the new materials industry.
[0004] The bio-based polymer materials with a higher marketization include polylactic acid, polyhydroxy fatty acids, polyhydroxyacetic acid, polybutylene glycol succinate (PBS), etc., which are mainly fatty polymers. Due to the lack of rigid aromatic rings in their molecular structure, their mechanical properties (such as strength, modulus, creep resistance, etc.) and heat resistance (such as thermomechanical properties, heat deformation temperature, etc.) are significantly lower than those of petroleum-based polymer materials such as polyethylene terephthalate (PET), aromatic nylon, polycarbonate, and phenolic resin, which seriously limits their application range.
[0005] If bio-based polymer materials want to partially replace and supplement petroleum-based polymer materials, it is urgent to introduce a rigid aromatic ring structure into their molecular structure. 5-Hydroxymethylfurfural (HMF), as the only bio-based platform compound with a ring structure, has become a hot topic in industry research in recent years. Its downstream derivatives 2,5-furandicarboxylic acid (FDCA) and tetrahydrofuran dimethanol (THFDM) have rigid aromatic rings and can be polymerized with monomers such as diols and diamines to prepare new bio-based polymer synthetic materials with excellent performance. For example, 100% renewable furandicarboxylic acid polyester (PEF) prepared from FDCA and bio-based ethylene glycol has excellent barrier properties, heat resistance, and mechanical properties. It can replace PET in films and soft drink bottles to extend the shelf life of packaging products; for example, the raw materials containing THFDM, 1,4-butanediol, and succinic acid are melt-polycondensed to obtain a degradable copolymer, which solves the problem of excessive degradation and poor mechanical properties of traditional biodegradable plastic PBS, and improves the versatility of PBS in the packaging field.
[0006] At present, the application market of bio-based polyfuran materials accounts for a small proportion. In the future, as the cost of HMF decreases, its application in the field of bio-based materials has great development potential. The research and development of new and more competitive polyfuran materials and the updating of process technology for the production of HMF and its derivatives require continuous resource investment and research and development. Summary of the invention
[0007] The object of the present invention is to provide a biomass-based polyfuran polymer material, which is composed of a carbon-carbon chain, a furan ring, and a COC bond, and the molecular structure is as follows:
[0008] It is a backbone carbon-carbon chain;
[0009] The backbone carbon-carbon chain consists of carbon-carbon single bonds and carbon-carbon double bonds.
[0010] The molecular weight of the polymer material is 1000-1000000, preferably 2000-1000000.
[0011] The polymer material has an absorption signal in the visible light or ultraviolet light region or in the ultraviolet-visible region.
[0012] The synthetic raw materials of the polymer material are bis-(5-formylfurfuryl) ether and ketone.
[0013] Furthermore, the types of ketones include monoketones, diketones, and polyketones. Monoketones are preferably acetone and cyclohexanone. Diketones are preferably diacetyl, hexanedione, and pentanedione. Polyketones are compounds having a carbon number greater than or equal to 4 and a carbonyl number greater than or equal to 3, preferably hexanetrione and heptanetrione.
[0014] Furthermore, the polymer material preparation process is: bis-(5-formylfurfuryl) ether and ketone are placed in a solvent, reacted under the action of a catalyst at a certain temperature for a period of time to obtain a polymer material.
[0015] Furthermore, the catalyst includes one or more of a base catalyst, a metal oxide catalyst or a metal salt catalyst.
[0016] Furthermore, the alkaline catalyst includes an inorganic base; preferably, the inorganic base includes one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate.
[0017] Furthermore, the metal oxide catalyst includes one or more of titanium oxide, vanadium oxide, cerium oxide, zirconium oxide, and tungsten oxide.
[0018] Furthermore, the metal salt catalyst includes one or both of vanadium chloride and chromium chloride.
[0019] Furthermore, the molar ratio of bis-(5-formylfurfuryl) ether to ketone is less than 1.5,
[0020] Furthermore, the molar ratio of the bis-(5-formylfurfuryl) ether to the ketone is 1 to 0.5.
[0021] Preferably, the molar ratio of the bis-(5-formylfurfuryl) ether to the ketone is 0.53-0.81.
[0022] Furthermore, the temperature in the preparation method is less than or equal to 250 degrees Celsius.
[0023] Furthermore, the temperature in the preparation method is less than or equal to 200 degrees Celsius.
[0024] Preferably, the temperature in the preparation method ranges from 50 degrees Celsius to 200 degrees Celsius.
[0025] Furthermore, the reaction time in the preparation method ranges from 0.5h to 600h.
[0026] Preferably, the reaction time in the preparation method ranges from 6 h to 72 h.
[0027] Furthermore, the solvent in the preparation method is water, an organic solvent or a mixture of the two.
[0028] Furthermore, the organic solvent includes alcohols, acetonitrile, ketones, halogenated alkanes, esters, and ethers, preferably alcohols, acetonitrile, 1,4-dioxane, and halogenated alkanes.
[0029] Furthermore, the alcohols include methanol and isopropanol; the ketones include acetone; the halogenated alkanes include dichloromethane and chloroform; the esters include ethyl acetate; and the ethers include 4-dioxane.
[0030] The beneficial effects of the present invention are:
[0031] The present invention provides a biomass-based polyfuran polymer material and a preparation method thereof, using bis-(5-formylfurfuryl) ether (OBMF), a downstream etherification product of HMF, as a raw material to synthesize a polymer material containing a furan ring, a carbon-carbon chain, and a COC group in the molecular skeleton, wherein COC is easily hydrolyzed under acid catalyst conditions and can be 100% recycled; in addition, the length of the carbon-carbon chain can be adjusted, thereby achieving flexible adjustment of the material; the material has an absorption signal in the visible or ultraviolet region. The structure of the polyfuran-based polymer material is different from that of the currently reported polyfuran-based polymer material, and it has advantages in the field of optoelectronic materials, and can also be used in the fields of energy materials, catalytic materials, packaging materials, adsorption materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1 is a high performance liquid chromatography analysis diagram of the condensation process of OBMF and acetone in Example 1;
[0033] Figure 2 The infrared spectra of OBMFA and OBMF of Example 1 are shown below;
[0034] Figure 3 For Example 1 OBMFA 13 C-NMR visible spectrum;
[0035] Figure 4 The UV-visible spectra of OBMFA and OBMF in Example 1 are shown below;
[0036] Figure 5 UV-visible spectra of OBMFH and OBMFC of Examples 5 and 6;
[0037] Figure 6 The infrared spectra of OBMFH and OBMFC of Examples 5 and 6 are shown. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below by taking the biomass-based polyfuran polymer material and its preparation method as an example. The protection content of this patent is not limited to the specific implementation method, but is limited by the claims.
[0039] Example 1
[0040] 50 ml ultrapure water and 125 ml methanol were added to a round-bottom flask, followed by 0.7 g Na2CO3 and 0.5 g OBMF. After they were completely dissolved, 0.2 g acetone was added and magnetically stirred at 50 degrees Celsius for 48 hours. After the reaction was completed, the mixture was washed with methanol / water and then filtered with ultrapure water. The solid obtained by filtration was dried at 70°C and recorded as OBMFA with a yield of 85%.
[0041] The consumption of raw materials in the preparation process was detected by high performance liquid chromatography, and it was found that the raw materials were completely consumed within 10 hours ( Figure 1 ).
[0042] The C=O, C=C, furan ring ( Figure 2 ), which is consistent with the predicted structure. The OBMFA structure is as follows:
[0043]
[0044] Using ultraviolet spectroscopy to analyze its structure, it is known that the material's absorption range is mainly in the ultraviolet region (200-700nm) ( Figure 3 ).
[0045] The molecular weight range of the material analyzed by GPC is 2000-100,000
[0046] Example 2
[0047] 50 ml ultrapure water and 200 ml methanol were added to a round-bottom flask, and then 0.1 g NaOH and 0.5 g OBMF were added. After they were completely dissolved, 0.3 g acetone was added and magnetically stirred at 50 degrees Celsius for 36 hours. After the reaction was completed, the mixture was washed with methanol / water and then filtered with ultrapure water. The solid obtained by filtration was dried at 70°C, and the yield was 88%. The structure and properties of the material were analyzed by infrared, ultraviolet, nuclear magnetic and other means, and the results were similar to those in Example 1.
[0048] Example 3
[0049] 50 ml ultrapure water and 125 ml methanol were added to a round-bottom flask, and then 0.8 g NaHCO3 and 0.5 g OBMF were added. After they were completely dissolved, 0.3 g acetone was added and magnetically stirred at 90 degrees Celsius for 36 hours. After the reaction was completed, the mixture was washed with methanol / water and then filtered with ultrapure water. The solid obtained by filtration was dried at 70°C, and the yield was 92%. The structure and properties of the material were analyzed by infrared, ultraviolet, nuclear magnetic and other means, and the results were similar to those in Example 1.
[0050] Example 4
[0051] 50 ml ultrapure water and 125 ml methanol were added to a round-bottom flask, followed by 0.7 g Na2CO3 and 0.5 g OBMF. After the mixture was completely dissolved, 0.2 g acetone was added, and the mixture was stirred magnetically at 50 degrees Celsius for 12 hours, and then at 200 degrees Celsius for 6 hours. After the reaction was completed, the mixture was washed with ultrapure water, and the solid obtained by suction filtration was dried at 70°C. The structure and properties of the material were analyzed by infrared, ultraviolet, nuclear magnetic and other means, and the results were similar to those in Example 1, with a yield of 96%.
[0052] Example 5
[0053] 50 ml ultrapure water and 125 ml methanol were added to a round-bottom flask, followed by 0.7 g Na2CO3 and 0.5 g OBMF. After the mixture was completely dissolved, 0.3 g hexanedione was added and magnetically stirred at 50 degrees Celsius for 24 hours. After the reaction was completed, the mixture was washed and filtered with methanol / water, and then washed and filtered with ultrapure water. The solid obtained by filtration was dried at 70 degrees Celsius. The material was recorded as OBMFH, and the yield was 90%. The structure and properties of the material were analyzed by infrared and ultraviolet methods. The results are as follows: Figure 5 , 6 The structural formula of OBMFH is as follows:
[0054] Example 6
[0055] Add 50ml ultrapure water and 125ml methanol to a round-bottom flask, then add 0.7g Na2CO3 and 0.5g OBMF, and after they are completely dissolved, add 0.35g cyclohexanone and stir magnetically at 50 degrees Celsius for 24h. After the reaction is completed, wash and filter with methanol / water, then wash and filter with ultrapure water, and dry the solid obtained by filtration at 70°C. The material is recorded as OBMFC, and the yield is 90%. The structure and properties of the material are analyzed by infrared and ultraviolet means. The results are as follows Figure 5 , 6 The structural formula of OBMFC is as follows:
[0056] Example 7
[0057] 50 ml ultrapure water and 125 ml 1,4-dioxane were added to a round-bottom flask, and then 0.7 g Na2CO3 and 0.5 g OBMF were added. After they were completely dissolved, 0.2 g acetone was added and magnetically stirred at 50 degrees Celsius for 72 hours. After the reaction was completed, the solid was washed with ultrapure water and filtered, and the solid obtained by filtration was dried at 70°C, with a yield of 89%. The results of analyzing its structure by infrared detection and ultraviolet spectroscopy were similar to those in Example 1.
[0058] Example 8
[0059] 50 ml ultrapure water and 125 ml acetonitrile were added to a round bottom flask, and then 0.7 g Na2CO3 and 0.5 g OBMF were added. After they were completely dissolved, 0.2 g acetone was added and magnetically stirred at 50 degrees Celsius for 72 hours. After the reaction was completed, the solid was washed with ultrapure water and filtered, and the solid obtained by filtration was dried at 70°C, with a yield of 95%. The results of analyzing its structure by infrared detection and ultraviolet spectroscopy were similar to those in Example 1.
[0060] Effect example
[0061] Example 1 Obtained OBMFA is insoluble in both methanol and water solvents. An appropriate amount of the solid sample is placed in a reactor, and 30 ml of 15% hydrochloric acid solution is added. The solid is stirred at room temperature, and the solid does not dissolve. The reactor is sealed and heated to 150 degrees and maintained for 2 hours. After the temperature is lowered to room temperature, the reactor is opened, and 60 ml of methanol is added. It is found that there is no solid in the liquid, indicating that the solid material is depolymerized.
[0062] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A biomass-based polyfuran polymer material, characterized in that: The molecular structure formula of the polymer material is: in It is a backbone carbon-carbon chain.
2. The biomass-based polyfuran polymer material according to claim 1, characterized in that: The backbone carbon-carbon chain consists of carbon-carbon single bonds and double bonds.
3. The biomass-based polyfuran polymer material according to claim 1, characterized in that: The molecular weight of the polymer material is 1000-1000000.
4. A method for preparing a biomass-based polyfuran polymer material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: placing bis-(5-formylfurfuryl) ether and ketone in a solvent, heating and reacting under the action of a catalyst, washing and drying, and obtaining a biomass-based polyfuran polymer material.
5. The method for preparing the biomass-based polyfuran polymer material according to claim 4, characterized in that: The ketone includes one or more of monoketone, diketone and polyketone; The monoketone includes acetone and cyclohexanone; The diketones include diacetyl, hexanedione, and pentanedione; The polyketone is a compound having 4 or more carbon atoms and 3 or more carbonyl groups.
6. The method for preparing the biomass-based polyfuran polymer material according to claim 4, characterized in that: The catalyst includes one or more of a base catalyst, a metal oxide catalyst or a metal salt catalyst; The base catalyst includes an inorganic base; the inorganic base includes one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate; The metal oxide catalyst includes one or more of titanium oxide, vanadium oxide, cerium oxide, zirconium oxide, and tungsten oxide; The metal salt catalyst includes one or both of vanadium chloride and chromium chloride.
7. The method for preparing the biomass-based polyfuran polymer material according to claim 4, characterized in that: The molar ratio of the bis-(5-formylfurfuryl) ether to acetone is less than 1.
5.
8. The method for preparing the biomass-based polyfuran polymer material according to claim 4, characterized in that: The temperature of the heating reaction is less than or equal to 250 degrees Celsius; and the reaction time is between 0.5h and 600h.
9. The method for preparing the biomass-based polyfuran polymer material according to claim 4, characterized in that: The reaction solvent is one or both of water and an organic solvent; the organic solvent includes alcohols, acetonitrile, ketones, halogenated alkanes, esters, and ethers.
Citation Information
Patent Citations
Polyfuran compound and preparation method thereof
CN106279673A
Preparation method of bis-(5-formyl furfuryl)ether and polyamide material
CN111233798A
Method for synthesizing high-viscosity bio-based furan polyester
CN117362611A
Composition of cathode materials for lithium-sulfur battery comprising mesoporous carbon-carbon wire structure and sulfur, producing method thereof and lithium-sulfur battery using it
KR1020220154894A